Analysis on Corrosion Products and Coating Shedding in Acid Gas Separator - LIU Qiang, REN Quan-you, MA Jun, GAO Qiu-ying, SHAO Yong-hua, SUN Hai-jiao, CAO Xian-long, ZENG Wen, LAN Wei (Cailiao Baohu)
In order to evaluate and analyze the internal corrosion of acid gas separator in an oil and gas field in Northwest China, the corrosion of the substrate and internal coating of an acid gas separator was investigated by using macroscopic and morphology observation, routine inspection, corrosion product element and composition analysis. Results showed that the obvious corrosion occurred in the investigated acid gas separator, and the dirt thickness of about 10 mm was accumulated on the bottom of the separator and the local corrosion pit could reached 0.5～1.0 cm. In addition, the internal coating was generally kept in good condition, but there were obvious discoloration, embrittlement and serious peeling-off in some areas. Especially, the damage under the water line of the separator was relatively serious. It was considered that the existence of acid corrosive media such as hydrogen sulfide in the service environment, the quality control of coating application process and the adaptability of the selected coating to the service environment might be the basic reasons for the corrosion of the acid gas separator. Finally, several suggestions were given for the corrosion prevention.